Evaluating the effectiveness of botanical sprays in controlling Aphids ( Brevicoryne brassicae ) on rape ( Brassica napus L. ) - Pahla, Innocent; Moyo, Martin; Muzemu, Simbarashe; Muziri, Tavagwisa (INNSpub, 2022)
Rape, Brassica napus (L) is widely grown in Zimbabwe. Rape aphids, Brevicoryne brassicae (Linn) is the most damaging pest on rape. The use of synthetic pesticides poses serious challenges to ecological and financial sustainability. The aqueous pesticidal plant extracts combinations of garlic and chilli were exploratory evaluated for efficacy and optimum dosage rate in controlling aphids on rape at Midlands State University. The experiment was arranged as a Randomised Complete Block design (RCBD) with six treatments i.e. 10g garlic + 10g chilli, 7.5 garlic + 7.5g chilli, 5g garlic + 5 g chilli, 2.5 g garlic + 2.5g chilli, Dimethoate 40% EC (positive control) and plain distilled water (negative control).The treatments were replicated six times. Cloves of garlic and chilli were pounded into a pulp in mortar. The extracts were prepared by mixing crude aqueous plant extracts and boiled distilled water at 0, 0.5, 1, 1.5 and 2% (w/v). Liquid soap was added at 0.1% in the mixture. Dimethoate was diluted at 0.1% (v/v). The extracts were kept for 24 hr at room temperature and sieved through nested sieves with aperture sizes of 710 and 250µm. Sprays were applied weekly once the aphids had naturally established within the crop. A systematic random sampling was used to select plants for aphid counting in each row with k-factor three from the net plot 24 hours post spraying. Aphid population data and yield were recorded. The results showed that botanical sprays significantly (p<0.05) affected aphid population and yield. There was a general decrease in aphid populations and an increase in yield with increase in crude aqueous extracts concentration, 10g garlic + 10g chilli recording the lowest aphid count and the highest yield. The study showed that Garlic and chilli extracts have some pesticidal effects on rape aphids